Response to Reduced Diurnal Variation of Heart Rate Is Associated With Increased Plasma B‐Type Natriuretic Peptide Level in Patients With Atrial Fibrillation. Issue 12 (17th October 2013) - Yalcinkaya, Emre; Celik, Murat; Yildirim, Erkan; Yasar, Salim; Bugan, Baris
<x xml:space="preserve">Abstract</x> Kamikawa S et al. Clin Cardiol. 2013;36:394–400